Plaque Erosion: A Distinctive Pathological Mechanism of Acute Coronary Syndrome - Luo, Xing; Lv, Ying; Bai, Xiaoxuan; Qi, Jinyu; Weng, Xiuzhu; Liu, Shaoyu; Bao, Xiaoyi; Jia, Haibo; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Plaque erosion (PE) is one of the most important pathological mechanisms underlying acute coronary syndrome (ACS). The incidence of PE is being increasingly recognized owing to the development and popularization of intracavitary imaging. Unlike traditional vulnerable plaques, eroded plaques have unique pathological characteristics. Moreover, recent studies have revealed that there are differences in the physiopathological mechanisms, biomarkers, and clinical outcomes between PE and plaque rupture (PR). Accurate diagnosis and treatment of eroded plaques require an understanding of the pathogenesis of PE. In this review, we summarize recent scientific discoveries of the pathological characteristics, mechanisms, biomarkers, clinical strategies, and prognosis in patients with PE.